2016
DOI: 10.12738/spc.2016.1.0005
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Psychotherapy Settings: A Phenomenological Inquiry into the Experiences of Turkish Health Professionals

Abstract: This study aims to explore the role of spirituality in psychotherapy using counselors' own experiences. A phenomenological approach was used to examine data from interviews completed by eight psychological counselors working in the counseling field in Istanbul, Turkey. Findings showed that counselors acknowledged the importance of discussing topics related to spirituality. Common reasons for engaging in spiritual discussions in treatment were outlined. Results suggest that developing skills and confidence to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Thus, aiming to promote spirituality in mental health settings can be a significant way to facilitate well-being and PTG following experiences of terrorism. However, as Eksi, Takmaz, and Kardas (2016) pointed out, consistent with research findings in other countries, mental health professionals in Turkey often lack training about how to transfer spirituality into the therapeutic process. Offering systematic training and supervision for integration of spiritual matters into the process might help to facilitate growth in all domains.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, aiming to promote spirituality in mental health settings can be a significant way to facilitate well-being and PTG following experiences of terrorism. However, as Eksi, Takmaz, and Kardas (2016) pointed out, consistent with research findings in other countries, mental health professionals in Turkey often lack training about how to transfer spirituality into the therapeutic process. Offering systematic training and supervision for integration of spiritual matters into the process might help to facilitate growth in all domains.…”
Section: Discussionmentioning
confidence: 55%
“…Results suggest that “developing skills and confidence to work with issues of spirituality is a complex and dynamic task” (Ekşi, Takmaz, & Kardaş, 2016). The experiences of participants in the hospitals and the health care system are consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of therapists have indicated that spirituality can be used therapeutically in the direction of the client's needs and guidance. In the qualitative study conducted by Ekşi, Takmaz, and Kardaş (2016) in Turkey, psychological counselors gave importance to spirituality in the counseling process, and stated reasons for the inclusion of spirituality in the therapeutic process. Developing standards for application and supervision is important for spiritually oriented psychotherapy in general, as well as spiritually oriented CBT specifically.…”
Section: Ethical Responsibility In Spiritually Oriented Cbt Practicementioning
confidence: 99%